Functional law of iterated logarithm for normalized integrals of processes with weak dependence - Bondarev, B. V.; Korolev, M. E. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
For normalized integrals of processes with weak dependence, we prove the law of iterated logarithm in the Strassen form. The results obtained are used for the construction of a curvilinear confidence region in which a solution of an equation with small parameter is sought.